In-situ preheating: Novel insights into thermal history and microstructure of directed energy deposition-arc of hot-work tool steels - Ulf Ziesing; Santiago Benito; Sebastian Weber; Jonathan Lentz (Journal of Materials Research and Technology)
Directed Energy Deposition-Arc (DED-Arc/M) represents a promising approach to the production of complex and medium-sized parts, eliminating the need for specific tooling and the minimization of resource use. However, the inherent thermal conditions of DED-Arc/M, characterized by high cooling rates and successive reheating cycles, result in microstructures distinctly different from those observed in traditional cast materials. Nevertheless, the influence of thermal history on DED-Arc/M processed hot-work tool steels remains an insufficiently addressed topic in previous studies. Therefore, this work systematically investigates the effects of heat input and accumulation through assessing the thermal history and resulting microstructural changes during DED-Arc/M processing of the hot-work tool steel AISI H13 (X40CrMoV5-1). Accordingly, layer-wise heat input results in heat accumulation, leading to high interpass temperatures, significantly impacting the solidification and, thus, the microsegregation as well as the overall chemical homogeneity. By employing an innovative statistical approach that incorporates quantitative EDS data, the distribution of chemical elements was investigated. Furthermore, a novel computational procedure through the utilization of empirical and thermodynamic calculations was used to identify microstructural effects on the thermodynamic stability of retained austenite. This research offers vital insights into the microstructural dynamics of tool steels processed through DED-Arc/M, underlining the pivotal role of precise thermal management in tailoring material microstructures and, consequently, influencing the properties for unlocking the full potential of additive manufacturing for industrial applications.